Business Plan : Catzonia / Aifa Ayunni Mohd Gous - Mohd Gous, Aifa Ayunni (2020)
Catzonia have been choose to opened up the business for cat hotel in city area at Kuala Lumpur. City area is market potential for Catzonia grown up the business because population of people is high and strategic places. Strategic places here because city area is the place for many people like to shopping, walking, eat for dinner and lunch, hang out with family or friends and so on. For that many people can see Catzonia of cat hotel was opened and they can try for Catzonia services especially for people have their own cat. City area is also strategic places for more people want to grown up their business from down but the services need to more good so that customers will appreciate and satisfied with this service. After that, when Catzonia get high response from customers from other city area, so that Catzonia have a good chance to forward the business at other areas.